Pre-infusion ferritin a predictive biomarker for CAR T-cell therapy in R/R multiple myeloma - Moreno-Cortes, Eider F.; Arribas, Mariano; Martinez-Gamboa, David A.; Figueroa-Aguirre, Juana; Patel, Rohan; Bihnam, Daniel; Yadav, Udit; Wiedmeier-Nutor, J. Erin; Bergsagel, Leif; Chhabra, Saurabh; Fonseca, Rafael; Castro, Januario E. (Frontiers in Hematology, 2025)
IntroductionEvaluating predictive biomarkers early in treatment, clinicians can anticipate Q7 77 78 survival outcomes. Ferritin has emerged as a promising predictor of clinical 79 outcomes in multiple myeloma (MM) patients undergoing chimeric antigen patient responses and tailor therapeutic strategies to enhance efficacy and 80 receptor (CAR) T-cell therapy.MethodsIn this study, we investigated the prognostic 81 value of ferritin and C-reactive protein (CRP) as biomarkers in CAR T-cell 82 83 ferritin and CRP levels at two time points pre-infusion (Day-0) and pre- 84 lymphodepleting chemotherapy (LDC) and their association with clinical therapy for MM. This study’s objective was to evaluate the correlation between 85 response outcomes. We retrospectively analyzed outcomes from 52 relapsed/ 86 refractory MM (RRMM) patients who received either idecabtagene vicleucel or 87 ciltacabtagene autoleucel CAR T-cell therapies.ResultsLow ferritin levels at Day-0 and 88 pre-LDC were able to predict better responses regardless of the CAR T cell 89 product (hazard ratio [HR] 0.01 (95% CI 0.05–0.5); p=0.001, (HR 0.05 95% CI 90 0.01-0.2, p=<0.0069), respectively. Low ferritin + low CRP were able to predict responses at Day-0 and pre-LDC HR 0.3 (95% CI 0.07-1.3); p=0.04, HR 0.26 (95% CI 0.03-2.1), p=0.04, respectively.DiscussionOur results indicate that ferritin and CRP 93 levels represent promising predictive biomarkers that may refine CAR T-cell 94 therapy response by enabling better patient stratification and personalized 95 treatment approaches. Our study underscores the need for their integration 96 into routine clinical practice for MM management.ConclusionsFuture prospective studies are 97 warranted to validate these findings and explore the mechanistic link between 98 99 100 101 102 elevated ferritin levels, immune activation states, and CAR T-cell efficacy.